Significant increase in cultivation of Gardnerella vaginalis, Alloscardovia omnicolens, Actinotignum schaalii, and Actinomyces spp. in urine samples with total laboratory automation - Klein, Sabrina; Nurjadi, Dennis; Heeg, Klaus; Zimmermann, Stefan; Burckhardt, Irene (European journal of clinical microbiology & infectious diseases, 2018)
We provide the first report in Europe of a large number of urine samples processed with TLA. TLA showed enhanced growth of non-classical and rarely cultured bacteria from urine samples. Our findings suggest that previously underestimated bacteria may be relevant pathogens for urinary tract infections. Further studies are needed to confirm our findings.
Gesehen am 30.10.2019